Health education in the adolescent segment from the perspective of active teaching-learning methodologies - Pacheco, Maria Inês Miranda (2019)
This study addressed the practice of health education, with emphasis on oral self-care and based on Active Teaching-Learning Methodologies (ATLM). The active methodologies present, among their characteristics, displacement of protagonism from the educator to the student, encouraging their insertion as the main responsible for their learning. It aimed to interact, discuss and promote health and self-care, with emphasis on oral health, according to the reality of the group of adolescents within the context of the Brazilian Unified Health System. The study included two workshops, involving participation of 40 adolescents, on different and sequenced days. It focused on the reflection of daily life, interests, needs and the social and cultural contexts of adolescents, aiming to stimulate a process of deconstruction/construction of knowledge, providing the search for new and different knowledge. The reported experience of educational practice was positively evaluated in the perception of students, and facilitated the dialogue and interaction between mediators and adolescents. There was intense participation of adolescents during the workshops and critical reflection on healthcare, related to life problems. The educational practice promoted the construction of shared possibilities in dealing with daily adversities and family conflicts, as it proved to be successful and full of critical-reflexive potentialities in health decision-making, according to adolescents’ standpoint.